An aesthetic rehabilitation of fractured anterior maxillary teeth with multiple diastema - Galih Sampoerno; Kezia Sepdwiningtyas Santoso; Agustina Restu Nurkhotimah; Karina Awanis Adla; Sri Kunarti; Adioro Soetojo; Nirawati Pribadi; Kun Ismiyatin (Conservative Dentistry Journal, 2025)
Background: Aesthetic issues on anterior maxillary teeth often require comprehensive treatment due to both functional and psychological impacts. This case report highlights the clinical approach and management for anterior maxillary teeth with crown fracture and multiple diastemas through restorative aesthetic procedures. Purpose: To describe a clinical approach and restorative aesthetic management for a 37 year-old female patient with a crown fracture and multiple diastemas on the anterior maxillary teeth, aiming to restore aesthetics and function through a carefully planned dental treatment. Case(s): A 37 year-old female patient presented to RSGMP UNAIR with a chief complaint of fractured upper anterior teeth and a history of intermittent pain. The patient also reported concern about the spacing between her upper front teeth. The clinical examination revealed involvement of teeth 13, 12, 11, 21, 22, and 23. The patient had no previous dental treatment and no systemic health issues. Case Management: A detailed clinical and radiographic examination was performed, followed by a comprehensive treatment strategy targeting tooth elements 13, 12, 11, 21, 22, and 23. The management focused on restoring tooth structure, closing the diastema, and improving smile aesthetics. Conclusion: Aesthetic and functional rehabilitation of the anterior maxillary teeth was planned and carried out through an integrative restorative approach. The case emphasizes the importance of proper diagnosis dan treatment planning in managing complex aesthetic cases.